Bifidobacterium species associated with breastfeeding alleviate neonatal hyperbilirubinaemia via the gut microbiota-α-linolenic and linoleic acid metabolism-enterohepatic circulation axis - Chunxiu Lin; Yugui Lin; Rui Xiao; Min Guo; Hao Zhang; Wei Chen; Gang Wang (Microbiome)
Abstract Background Recent studies suggest a role of gut microbiota in the development of neonatal hyperbilirubinemia, with bifidobacteria showing promise in alleviating symptoms. However, uncertainties persist regarding gut bifidobacterial species composition and their effects on bilirubin metabolism. Therefore, the study investigated the association between the gut microbiota and neonatal hyperbilirubinemia, assessing the potential and underlying mechanisms of Bifidobacterium in managing the condition. Results Compared to the high-risk group (requiring clinical intervention), low-risk neonates (designated as controls without therapeutic needed) demonstrated a higher abundance of breastfeeding-associated Bifidobacterium species, including Bifidobacterium longum subsp. infantis, B. bifidum, and B. breve. In an experimental neonatal hyperbilirubinemia rat model, these Bifidobacterium species’ protective effects were demonstrated by reducing serum bilirubin levels, maintaining growth and development, and improving neurobehavioral reflexes. These benefits are associated with improved liver and intestinal barrier functions and reduced enterohepatic circulation of bilirubin. Among the various treatment groups, B. longum subsp. infantis exhibited the most potent effect, followed by B. bifidum and B. breve. Intestinal metabolism analysis revealed that the levels of arachidonic acid and docosahexaenoic acid were increased and negatively correlated with bilirubin levels. These findings were further confirmed in the neonatal cohort study. Direct supplementation of these metabolites into the colon of neonatal rats improved disease phenotypes. In addition, both in vitro and in vivo experiments demonstrated the specific inhibitory effect of arachidonic acid and docosahexaenoic acid on β-glucuronidase enzyme activity. Notably, both in vitro intestinal fermentation models and genomic analyses demonstrated that the three Bifidobacterium species cannot synthesize these unsaturated fatty acids due to the lack of related genes. However, data suggested that these species might promote the accumulation of arachidonic acid and docosahexaenoic acid by regulating the gut microbiota’s structure and function. Moreover, these species show species-specific genomic distribution patterns, which might influence the gut microbiota's α-linolenic and linoleic acid metabolism pathways, thereby affecting bilirubin levels. Conclusions The results indicate that Bifidobacterium species associated with breastfeeding can prevent neonatal hyperbilirubinemia by regulating the gut microbiota–α-linolenic and linoleic acid metabolism–enterohepatic circulation axis, increasing gut metabolites arachidonic acid and docosahexaenoic acid, and reducing the enterohepatic circulation of bilirubin. Video Abstract